2002
DOI: 10.1159/000063092
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Gene Insertion/Deletion Polymorphism in Kuwaiti Children with Retinopathy of Prematurity

Abstract: Retinopathy of prematurity (ROP) is a disease characterized by neovascularization which occurs in infants with short gestational age and low birth weight and can lead to retinal detachment and blindness. In a proportion of ROP cases, the disease progresses to advanced stages despite rigorous intervention. The genotypes for angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism were determined in 181 premature Kuwaiti infants using a polymerase chain reaction (PCR) method. The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Hence, it is likely that these two disorders have a similar aetiology. In support of this, it was recently reported that in some cases, advanced ROP is associated with mutations in the ND (15)(16)(17)(18)(19)(20) gene which when mutated also causes X-linked FEVR (3,9,23). The present study provides additional evidence that mutations in FZD4 may cause a small fraction of sporadic FEVR and ROP cases.…”
Section: Genetic Variants Of Frizzled-4 Gene In Familial Exudative VIsupporting
confidence: 86%
“…Hence, it is likely that these two disorders have a similar aetiology. In support of this, it was recently reported that in some cases, advanced ROP is associated with mutations in the ND (15)(16)(17)(18)(19)(20) gene which when mutated also causes X-linked FEVR (3,9,23). The present study provides additional evidence that mutations in FZD4 may cause a small fraction of sporadic FEVR and ROP cases.…”
Section: Genetic Variants Of Frizzled-4 Gene In Familial Exudative VIsupporting
confidence: 86%
“…In one study, the homozygous ACE-ins allele was more frequently found in 74 preterm infants with ROP compared to 107 control infants. In infants without spontaneous regression of ROP (n = 21) the homozygous ACE-del allele was significantly more prevalent [8] . We were not able to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported adverse respiratory outcomes of preterm infants associated to the ACE-ins/del polymorphism [4][5][6] , whereas other researchers were not able to confirm these findings [7] . Furthermore, the ACEins/del polymorphism was reported to be associated with retinopathy of prematurity [8] and a reduced insulin sensitivity in healthy preterm and term neonates [9] . The AA and AC genotype of the ATR1166A/C polymorphism was found to be associated with persistent ductus arteriosus in preterm infants [10] .…”
mentioning
confidence: 99%
“…However, studies [38,39] do not support the association of this polymorphism and the risk of advanced ROP in different populations. Similarly, angiotensin-converting enzyme gene polymorphism is found to be associated with ROP in Kuwaiti population [16] but not in the other population [40,41]. Additionally, suggestive association has been reported between AGTR1 (encodes angiotensin II type I receptor), IHH (Indian Hedgehog), TBX-5 (T-box 5), glycoprotein Ib alpha polypeptide (GP1BA) and cholesterol ester transfer protein (CETP) and development of ROP [42].…”
Section: Association Of Other Genes With Ropmentioning
confidence: 99%